Behavioural and faecal glucocorticoid metabolite responses of single caging in six cats over 30 days. Issue 1 (10th November 2014) - Ellis, J. J.; Protopapadaki, V.; Stryhn, H.; Spears, J.; Cockram, M. S.
Abstract : Objectives: The aim was to characterize the behaviour and faecal glucocorticoid metabolite (FGM) responses of six cats (Felis catus) to single caging for 30 days. Design: In this observational study, changes in outcome measures were monitored with habituation to caging. Continuous focal observations of the activity, location in the cage, and posture were conducted from video recordings for one 24‐hour period/week/cat. Cat‐Stress‐Scores were recorded daily. All faecal samples were collected for analysis of FGM. Results: The percentage time spent eating increased, while percentage time spent grooming decreased, from week 1 to week 2. Cat‐Stress‐Score declined significantly from week 1 to week 2. FGM concentrations were significantly greater in week 1 than in week 5. A posthabituation time budget of the behaviour of the cats in the single cages showed that inactivity dominated the time budget and the cats were located on the shelf almost half of the time. Conclusions: Results suggests that a shelf was a resource of value to the cats, and that its inclusion in enclosure design is important. Quantitative and qualitative behavioural data indicated that there was an initial stress response to caging that stabilised after the first week, while FGM concentration took longer to stabilise.